Study on the residual service life of two pedestrian walkways located in BR-101 / PE (Research, Society and Development, 2021)
The road modal stands out as the most used system in Brazil for cargo transportation and people. Thus, it is extremely important to ensure resources for the maintenance of highways and their Special Engineering Structures - SES (bridges, viaducts and pedestrian walkways). The latter, which are the object of this study, play an indispensable role for the safety and comfort of users who cross the highways. However, it is possible to verify that a considerable number of these structures are in very poor conservation conditions, either due to the deterioration that occurs over time, structural deficiencies resulting from vehicle collisions, vandalism, or other factors that affect their useful life. In this sense, this paper aims to estimate the service life of two concrete footbridges located on federal highway BR-101/PE, by applying the concept of service life established by ISO 15686 (2011), NBR 15575-1 (ABNT, 2021) e NBR 15575-2 (ABNT, 2013). For this purpose, data obtained from the DNIT's Special Structures Management System (SGO) were used. The information on the anomalies and the respective structural stability conditions enabled the use of the Factor Method to obtain the estimated and residual service life of the studied works. The results obtained showed that the methodology can be employed in case studies in which there is no history of regular inspections of SES.